The association between glyceraldehyde-derived advanced glycation end-products and colorectal cancer risk. - Kong, S; Takeuchi, M; Hyogo, H; McKeown-Eyssen, G; Yamagishi, S; Chayama, K; O'Brien, P; Ferrari, P; Overvad, K; Olsen, A; Tjønneland, A; Boutron-Ruault, M; et al. (American Association for Cancer Research, 2015)
Background A large proportion of colorectal cancers are thought to be associated with unhealthy dietary and lifestyle exposures, particularly energy excess, obesity, hyperinsulinemia, and hyperglycemia. It has been suggested that these processes stimulate the production of toxic reactive carbonyls from sugars such as glyceraldehyde. Glyceraldehyde contributes to the production of a group of compounds known as glyceraldehyde-derived advanced glycation end-products (glycer-AGEs), which may promote colorectal cancer through their proinflammatory and pro-oxidative properties. The objective of this study nested within a prospective cohort was to explore the association of circulating glycer-AGEs with risk of colorectal cancer. Methods A total of 1,055 colorectal cancer cases (colon n = 659; rectal n = 396) were matchced (1:1) to control subjects. Circulating glycer-AGEs were measured by a competitive ELISA. Multivariable conditional logistic regression models were used to calculate ORs and 95% confidence intervals (95% CI), adjusting for potential confounding factors, including smoking, alcohol, physical activity, body mass index, and diabetes status. Results Elevated glycer-AGEs levels were not associated with colorectal cancer risk (highest vs. lowest quartile, 1.10; 95% CI, 0.82–1.49). Subgroup analyses showed possible divergence by anatomical subsites (OR for colon cancer, 0.83; 95% CI, 0.57–1.22; OR for rectal cancer, 1.90; 95% CI, 1.14–3.19; Pheterogeneity = 0.14). Conclusions In this prospective study, circulating glycer-AGEs were not associated with risk of colon cancer, but showed a positive association with the risk of rectal cancer.